AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN DADAP SEREP (Erythrina lithosperma Miq.) TERHADAP PERTUMBUHAN Escherichia coli - Asep Abdul Rahman; Ridwan Firmansyah; Lulu Setyabudi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2018)
Dadap Serep (Erythrina lithosperma Miq.) is one of the plants containing secondary metabolites in the form of alkaloids, flavonoids and tannins. Empirically dadap serep can be used to treat fever, abdominal pain, breast milk, prevent miscarriage, inflammation and cough. The aim of this research is to know the activity of ethanol extract in dadap serep (Erythrina lithosperma Miq.) in inhibiting growth of Escherichia coli ATCC 8939. The dadap serep leaves were extracted by maceration method using 96% ethanol solvent. The leaf thickness extract of dadap serep with concentration of 20%, 40%, 60% and 80% tested its antibacterial activity against growth of Escherichia coli ATCC 8939 using paper disc diffusion method. The result of concentration of leaf extract of dadap serep, obtained rendemen as much as 23,53%. Then the result of antibacterial activity test showed that leaf extract of dadap serep with concentration of 20% had no inhibition to growth of Escherichia coli ATCC 8939, while at concentration extract 40%, 60%, and 80% had inhibitory to growth of Escherichia coli ATCC 8939 with category weak resistor response.Keywords: Dadap serep (Erythrina lithosperma Miq.), Antibacterial activity, Escherichia coli ATCC 8939